STRATEGIC OPTIMIZATION OF RELIGIOUS MORNING ACTIVITIES TO STRENGTHEN ELEMENTARY STUDENTS' RELIGIOUS CHARACTER - Agustiana Putri, Dya Ayu; Yuliana Sari, Eka; Devi Asriyanti, Frita (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
The rapid advancement of the Society 5.0 era demands that elementary schools focus not only on academic achievement but also on the development of students’ religious character. This Community Service Program (PKM) aimed to optimize morning religious activities as a strategic effort to strengthen the religious values of students at SDN 1 Tawing, Tulungagung. The activities were carried out in April 2025 using a Participatory Action Research (PAR) approach, involving collaboration among teachers, students, and school stakeholders. The methods implemented included planning, execution, and reflection on morning routines such as congregational prayer, Dhuha prayer, recitation of short Qur’anic verses, and storytelling of exemplary Islamic figures. A total of 67 elementary students from grades 3, 4, and 5 participated in the program. Data were collected through pre-test and post-test questionnaires consisting of ten indicators of religious behavior. The results showed a significant increase in students’ average scores from 2.64 to 3.60. The highest improvement (+1.07) was observed in students’ awareness that morning religious routines help build noble character. These findings indicate that structured and consistently implemented religious activities have a positive impact on the internalization of religious values in students. The implications of this program suggest that schools should adopt spiritually-based routines systematically as part of the school culture to develop students’ religious behavior and moral awareness in facing the challenges of the digital era.